Wacana Kelompok Agama Marginal Eks Syiah Sampang dalam Media Lokal Madura - Aqil, Hasan Labiqul (Mu'ashir: Jurnal Dakwah dan Komunikasi Islam, 2024)
This article examines local cyber media coverage in Madura about the ex-Shiite group in Sampang. Although Indonesia guarantees freedom of religion, religion-based conflicts still occur, especially the marginalization of minority groups. Through the Critical Discourse Analysis (CDA) approach, this research explores how the media discourses on the ex-Sampang Shia and shapes people's perceptions. The research highlights that the media not only reflects, but also shapes social structures through language and narrative choices. The results show the power of majoritarianism ideology and the role of the media in perpetuating social conflict. The research emphasizes the need for independent and ethical media in promoting dialogue, tolerance and social inclusion.